A child’s right to basic education during the Covid-19 pandemic : a comparative analysis and evaluation of the impact of Covid-19 on the South African education system, and the effectiveness of the nation’s legal response in protecting a child’s right to education - Padachey, Denisha (Stellenbosch : Stellenbosch University, 2023)
Thesis (LLM)--Stellenbosch University, 2023.